Врахування поведінкових аспектів при розробці стратегії збуту - Нижник, Тарас Юрійович; Стеценко, Вікторія Анатоліївна (My University, 2019)
Метою статті є визначення поведінкових аспектів збуту підприємства у та розкриття сутності цього поняття як економічної категорії. Актуальність цієї теми полягає у тому, що не всі підпри- ємства в Україні повноцінно використовують збутову діяльність, оскільки визначення поведінки спо- живачів та врахування індивідуальних особливостей може задовольнити їхні потреби та збільшити продуктивність підприємства, що значною мірою вплине на його позиціонування на ринку. У статті визначено, що саме дозволяє враховувати поведінкові аспекти під час розроблення стратегії збуту продукції. Зроблено акцент на тому, які основні цілі стратегії збуту та чим саме забезпечується цей механізм у торговельному бізнесі. Розглянуто, які саме стратегії є та чим вони відрізняються, які елементи необхідні для їхньої повноцінної реалізації та на яких рівнях здійснюється збутова діяль- ність. Переконалися у можливості застосування методу «мозкового штурму» та методу «Дельфі». The main purpose of the article is to determine the behavioral aspects of the sale of an enterprise and to reveal the essence of this concept as an economic category. The relevance of this topic is that not all enterprises in Ukraine make full use of marketing activities, since defining consumer behavior and taking into account individual characteristics can satisfy their needs and increase the productivity of the enterprise, which will greatly influence their attitude to it. It looks at what strategies exist and how they differ, what elements are necessary for their full implementation, and at what levels of marketing activities. Be convinced of the possibility of using the method of “brainstorming” and the “Delphi” method. It is determined that behavioral aspects are the core around which all types of production and economic activity are concentrated. In addition, a strategy is sometimes seen as a bluff or a cunning maneuver that defines it as a tool of some type to win the competition. According to this view, it is possible to develop a “bluff strategy” to drag a competitor “to the dark path”, which does not lead anywhere. This is based on a purely psychological aspect - the desire to introduce into your organization something that has produced positive results for a competitor. The article defines what exactly allows to take into account behavioral aspects when developing a product marketing strategy. Emphasis is placed on what the main goals of the sales strategy are, and how this mechanism stands out in the trading business. The article deals with the question of what exactly allows to take into account behavioral aspects when developing a product marketing strategy and what distinguishes this mechanism in the trading business. The debate is being replaced by a program of individual polls, which are mostly conducted in the form of peer review tables. The experts’ answers are summarized and passed back to them (sometimes with new information about the object), after which the experts refine their answers. This procedure is repeated several times until they reach an acceptable convergence of all the opinions expressed. This method will help build an adequate model for the future development of the forecasting object.
Keywords: кафедра маркетингу; система збуту; стратегія збуту; збутова політика; канали збуту; поведінка споживачів; sales system; sales strategy; sales policy; sales channels; consumer behavior